A numerical method for solving Jaulent-Miodek equation - Kaya, D; El-Sayed, SM (Elsevier, 2003)
This Letter presents a numerical method, based on the Adomian's decomposition method (ADM), is presented of the Jaulent-Miodek (JM) equation. We obtain the numerical and exact travelling wave solutions of the JM equation for the initial conditions. The ADM method provides a better approximation to the exact solution than the classical methods. In order to show the efficiency of this method, exhaustive numerical examples are presented. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Jaulent-Miodek equation; numerical solution of differential equations; exact traveling wave solutions; Adomian's decomposition method; Adomian's polynomials